Perbedan Terapi Madu dan Multi Vitamin Terhadap Kadar Hemoglobin, Albumin dan Status Nutrisi Pada Anak Balita: Differences in Honey and Multi-Vitamin Therapy on Hemoglobin, Albumin and Nutritional Status in Toddlers - Meri Neherta (NERS Jurnal Keperawatan, 2011)
Intake of good nutrition plays an important role in achieving optimal body growth. Optimal body growth also includes brain development, which determines someone's intelligence. A factor that is most visible in the community is the lack of a mother’s knowledge about the nutritional intake required for children during their growth period. The research design used in this study is simple experiments. The research was conducted from May to September 2011 in the work areas of Nanggalo Health Center, Padang. The population in this research includes all toddlers in the work areas of Nanggalo Health Center, Padang. The sample size is 60 toddlers, where 30 toddlers received multivitamin therapy, and 30 others received honey therapy for 30 days. After performing the Friedman test, both groups showed the same significance level (P < 0.05), which means there was no significant difference between group 1 and group 2. To determine which group had the most significant effect, a Wilcoxon test was conducted. The conclusion of this research indicates that the therapeutic effect of multivitamins is better than honey therapy combined with vitamin B complex on hemoglobin levels, albumin levels, and nutritional status (w/U) in toddlers in the work areas of Nanggalo Health Center, Padang, in 2011. It is recommended for health workers to provide counseling to the community to encourage the use of multivitamins for toddlers to supplement their nutritional needs for growth and development. Multivitamins are readily available and affordable for the public.